Performance of the ASAS-proposed Cut-offs for Positive MRI Typical of Axial Spondyloarthritis for Discriminating Axial Involvement in Patients with Psoriatic Arthritis - Xianfeng Yan; Isaac T Cheng; Jacqueline So; Ho So; Ryan Ka Lok Lee; James Francis Griffith; Lai-Shan Tam (Journal of Clinical Rheumatology and Immunology)
Background: Unlike axial spondyloarthritis (axSpA), no classification criteria are currently available for axial psoriatic arthritis (axPsA). This study aimed to evaluate the performance of the proposed cut-offs from the Assessment of Spondyloarthritis International Society (ASAS) data-driven definitions for active and structural magnetic resonance imaging (MRI) lesions typical of axSpA in distinguishing axial involvement in patients with psoriatic arthritis (PsA). Methods: Seventy-two consecutive PsA patients (67% male, aged 45± 14 years) meeting the CASPAR classification criteria, regardless of the presence of back pain, were included. All patients underwent radiography of the pelvis and spine, as well as sacroiliac joint (SIJ) MRI, while 52 (72%) of 72 patients also underwent whole-spine MRI. The final diagnosis of axPsA was ascertained by two experienced rheumatologists. One rheumatologist with expertise in imaging and one trained reader evaluated the radiography and MRI images. Results: AxPsA was diagnosed in 27/72 (38%) patients. The proposed cut-offs for active sacroiliitis demonstrated high specificity (95.6%) but relatively low sensitivity (51.9%) in distinguishing patients with and without axPsA. When structural lesions of the SIJ were included in addition to active lesions, the sensitivity significantly improved (96.3% vs. 51.9%) with a modest decrease in specificity (86.7% vs. 95.6%). Incorporating MRI spine lesions (using the proposed cut-offs for positive spine MRI from the SPACE cohort) alongside SIJ lesions did not further change sensitivity or specificity compared with assessing SIJ alone. Conclusion: The ASAS-proposed cut-offs for identifying active and structural lesions of SIJ demonstrated satisfactory performance in discriminating axial involvement in PsA patients.